The Royal Bafokeng nation, a Case Study for the resource Curse - Thompson, Louise Frances (School of Economics, 2015)
Resource curse literature examines the causes and consequences of natural resources on economies. Within the literature, politico-economic theories provide insight into the relationship between institutional strength, the incentives facing the political elite due to the natural resource and the potential outcome for natural resource abundant economies. This paper argues that the Bafokeng Nation of South Africa provide an unusual case study for the resource curse. The Bafokeng's institutional strength is examined and the incentives facing the elite are analysed using Dunning's model. Dunning proposes three explanatory variables to explain the incentives facing the political elite (a) Volatility of Resource Revenues, (b) Societal Opposition to State Elites and (c) Prior Development of Non-resource Sectors. The Bafokeng are examined in light of Botswana to provide a comparative analysis. The analysis is supported by a Household survey of the Bafokeng, interviews with Bafokeng members as well as literature on both the Bafokeng and Botswana. The paper concludes that the institutional strength of the Bafokeng stems from their Tswana origins (similar to that of Botswana) and the current use of traditional governance structures, as well as the external constraints provided by the South African political system. Using Dunning's model this paper predicts that there would be diversification of the economy, political stability and mixed economic and fiscal stability. This however is strengthened by the unusual position of the Bafokeng as constrained by external factors as well as the internal strength provided by the traditional governance structures.